Efficient tri-metallic oxides NiCo2O4/CuO for the oxygen evolution reaction. Issue 72 (20th December 2019) - Mugheri, Abdul Qayoom; Tahira, Aneela; Aftab, Umair; Bhatti, Adeel Liaquat; Memon, Nusrat Naeem; Memon, Jamil-ur-Rehman; Abro, Muhammad Ishaque; Shah, Aqeel Ahmed; Willander, Magnus; Hullio, Ahmed Ali; Ibupoto, Zafar Hussain
Abstract : In this study, a simple approach was used to produce nonprecious, earth abundant, stable and environmentally friendly NiCo2 O4 /CuO composites for the oxygen evolution reaction (OER) in alkaline media. Abstract : In this study, a simple approach was used to produce nonprecious, earth abundant, stable and environmentally friendly NiCo2 O4 /CuO composites for the oxygen evolution reaction (OER) in alkaline media. The nanocomposites were prepared by a low temperature aqueous chemical growth method. The morphology of the nanostructures was changed from nanowires to porous structures with the addition of CuO. The NiCo2 O4 /CuO composite was loaded onto a glassy carbon electrode by the drop casting method. The addition of CuO into NiCo2 O4 led to reduction in the onset potential of the OER. Among the composites, 0.5 grams of CuO anchored with NiCo2 O4 (sample 2) demonstrated a low onset potential of 1.46 V vs. a reversible hydrogen electrode (RHE). A current density of 10 mA cm −2 was achieved at an over-potential of 230 mV and sample 2 was found to be durable for 35 hours in alkaline media. Electrochemical impedance spectroscopy (EIS) indicated a small charge transfer resistance of 77.46 ohms for sample 2, which further strengthened the OER polarization curves and indicates the favorable OER kinetics. All of the obtained results could encourage the application of sample 2 in water splitting batteries and other energy related applications.